2002
DOI: 10.1039/b202372p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of palladium hydrido-solvento complexes, including a key intermediate in the catalytic methoxycarbonylation of ethene to methyl propanoate

Abstract: The sequence of reaction steps and the role of each reactant, required for the transformation of the Pd( 0] ϩ , 2a, the active Pd()-hydride catalyst for the methoxycarbonylation of ethene to methylpropanoate, have been delineated using a combination of spectroscopic and crystallographic methods. The preparation and characterisation of a variety of related complexes are described including some unusual examples involving bidentate sulfonate complexes and mono-cationic and neutral palladium hydride complexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 22 publications
9
97
0
Order By: Relevance
“…We note that the dihydride [Pd(H) 2 (bcope)] would be PHIP active because of the second order nature of its hydride ligands. 72 Hence, as it is not detected, we can conclude that it is either too reactive to be seen, which is unlikely given the previous observation of ( t BuCOPE)Pd(H) 2 or that the contribution of a dihydride based reaction pathway is minimal in agreement with earlier literature predictions. 57,73 We conclude therefore that PHIP reflects an ideal platform from which to study this methoxycarbonylation reaction and thereby establish its potential to follow a wider range of catalytic processes than was previously thought possible.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We note that the dihydride [Pd(H) 2 (bcope)] would be PHIP active because of the second order nature of its hydride ligands. 72 Hence, as it is not detected, we can conclude that it is either too reactive to be seen, which is unlikely given the previous observation of ( t BuCOPE)Pd(H) 2 or that the contribution of a dihydride based reaction pathway is minimal in agreement with earlier literature predictions. 57,73 We conclude therefore that PHIP reflects an ideal platform from which to study this methoxycarbonylation reaction and thereby establish its potential to follow a wider range of catalytic processes than was previously thought possible.…”
Section: Discussionsupporting
confidence: 77%
“…1 High molecular weight thermoplastics, and the production of methylpropanoate 2 , reflect other high value products that are formed on an industrial scale via this reaction, which is most clearly illustrated by Lucite's Alpha process, one of the many successes of palladium catalysis. In addition, the alkoxycarbonylatyion of 1-alkynes finds a further role in the formation of unsaturated carboxylic acids that feature as building blocks in a range of situations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clegg et al [14] and Eastham et al [15] showed that the palladium catalysed methoxycarbonylation of ethylene follows the hydride cycle (A) which represents the predominant route to MeP formation. The Pd-hydride reacts with ethylene to form the…”
Section: Formulation Of Candidate Kinetic Modelsmentioning
confidence: 99%